Minimum wages as a mechanism for gender pay equity: the role of gender in predicting labour market outcomes from the minimum wage in south Africa's retail and agricultural sectors - Nicklin, Jessica (School of Economics, 2025)
Do minimum wages promote greater equity in pay in a developing country context? This paper seeks to answer this question through employing two diﬀerence-in-diﬀerence (DID) regression techniques to uncover the gendered impact of South Africa's Sectoral Wage Determinations (‘sectoral minimum wages' hereafter) on real hourly wages over the period 2001-2007 and establish whether these minimum wage laws reduced gender pay gaps among covered workers. The gender-speciﬁc eﬀects of minimum wages on employment, hours worked, and written contract coverage are also explored. The sectors analysed are the retail and agricultural sectors both of which employ a fairly equal share of men and women, who are similar across several characteristics. Furthermore, examining these two sectors oﬀers a unique opportunity to investigate whether a more “blanket” minimum wage is better suited to reducing gender pay discrepancies compared to multiple minimum wage schedules determined by various factors. For the agricultural sector, sectoral minimum wages were only set according to area (resulting in 2 minimum wage schedules), while for the retail sector, minimum wages were established according to occupation, hours worked, ﬁrm size and area (resulting in a total of 96 minimum wage schedules over the period of analysis). This paper ﬁnds that sectoral minimum wages had no signiﬁcant impact on the employment of men or women in the retail and agricultural sectors. Descriptive results indicate that the gender wage gap marginally increased among retail workers following the implementation of minimum wages. The regression analysis reﬂects this ﬁnding, as men experience greater gains in wages relative to women in areas where the median wage falls further below the minimum wage (i.e., where the minimum wage is more binding). In contrast, the descriptive ﬁndings suggest that the gender wage gap reduced signiﬁcantly among agricultural workers. The regression results mirror these results – one DID speciﬁcation reveals that women in the agricultural sector reap signiﬁcant improvements in their wages, while no signiﬁcant eﬀect is found for men. The other DID speciﬁcation indicates that both men and women in areas where the minimum wage is more binding experience greater improvements in their wages; however, women experience slightly greater increases. No signiﬁcant eﬀect is shown for women using this speciﬁcation. In terms of hours worked, men in the retail sector experience signiﬁcant improvements in their working hours, whereas women endure signiﬁcant declines. The opposite holds true for the agricultural sector. The above ﬁndings possibly suggest that a more “blanket” minimum wage may contribute to fostering greater gender equity in pay. Conversely, minimum wages set according to factors such as occupation may lead to the exacerbation of gender pay disparities. Nevertheless, there may be other diﬀerences between the retail and agricultural sectors that explain the disparities in the impact of sectoral minimum wage laws. While minimum wage violation (both in terms of incidence and depth) appears to be fairly similar among men and women (although slightly higher for women) – non-compliance rates are staggeringly high, especially among agricultural workers. This ﬁnding underscores the need for stricter monitoring and enforcement of minimum wages in South Africa.